The retreat from government support for social dialogue in the Australian public service - Forsyth, Anthony (2003)
This article explores the impact of the Coalition government's federal public sector reforms since 1996 in the Australian Public Service (APS). Under the Labor governments from 1983 to 1996, a range of measures operated to facilitate the development of social dialogue practices in the APS. There were also various mechanisms for consultation, information sharing and employee participation in decision-making, such as the Joint Council and Departmental Councils, statutory provisions for Industrial Democracy Plans, award provisions for consultation over business restructuring and support for consultative structures under enterprise bargaining and health and safety legislation. Nearly all of these measures have bee dismantled or downgraded since the Coalition government came to office, especially those requiring consultation with trade unions or providing unions with a central role in participative mechanisms. It is argued here that the government's reforms have involved a substantial reduction in formal support for social dialogue in the APS, and a rejection of the benefits that such an approach offers. - Reproduced.
Keywords: Public administration - Australia; Public administration